PROFILE OF HISTOPATHOLOGY OF CERVICAL CANCER TISSUES IN PATIENTS OF THE DR PIRNGADI MEDAN HOSPITAL - Sry Astuty Hasugian; Khairiza Lubis; Hau V Doan (JBIO: jurnal biosains (the journal of biosciences), 2020)
Cervical cancer is a malignant neoplasm that happened in the cervical area.  Several types of cervical cancer that usually happens in women such as squamous cell carcinoma (SCC), adenocarcinoma, adenosquamous carcinoma and neuroendocrine carcinoma. Therefore, this study aims to determine a descriptive description of the histopathological profile of cervical cancer tissue from patients that registered in the Anatomical Pathology Laboratory at the DR. Pirngadi Medan Hospital, in the period of 2019. The type of our research is retrospective descriptive with the sampling technique, namely total sampling. The sample used was cervical cancer tissue obtained from the biopsy and surgery on patients who were registered from January 2019 to December 2019, totaling 18 samples. Based on the descriptive histopathological description, we found three types of cervical cancer tissue: squamous cell carcinoma (55.5%), adenocarcinoma (38.8%) and adenosquamous carcinoma (5.5%). The neuroendocrine carcinoma type did not find in this present study. Of three types of these cervical cancer, we got that cervical cancer patients are women aged between 36-72 years, with an average age of 54 years.